2021
DOI: 10.1002/14651858.cd013639.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic imaging tests for the diagnosis of COVID-19

Abstract: Background The respiratory illness caused by SARS‐CoV‐2 infection continues to present diagnostic challenges. Our 2020 edition of this review showed thoracic (chest) imaging to be sensitive and moderately specific in the diagnosis of coronavirus disease 2019 (COVID‐19). In this update, we include new relevant studies, and have removed studies with case‐control designs, and those not intended to be diagnostic test accuracy studies. Objectives To evaluate the diagnostic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
1
15

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(124 citation statements)
references
References 116 publications
4
104
1
15
Order By: Relevance
“…Another small study found an 86.2% RT-PCR sensitivity in symptomatic COVID-19 patients in comparison with convalescent antibody [ 24 ]. Interestingly, a recent Cochrane meta-analysis on thoracic imaging of COVID-19 patients found an 87.9% pooled sensitivity for chest CT and 80.6% for chest X-ray [ 25 ]. However, diagnostic imaging is mainly performed on inpatients that can overestimate the sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Another small study found an 86.2% RT-PCR sensitivity in symptomatic COVID-19 patients in comparison with convalescent antibody [ 24 ]. Interestingly, a recent Cochrane meta-analysis on thoracic imaging of COVID-19 patients found an 87.9% pooled sensitivity for chest CT and 80.6% for chest X-ray [ 25 ]. However, diagnostic imaging is mainly performed on inpatients that can overestimate the sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with active Covid-19 were defined as those with positive real-time reverse transcriptasepolymerase chain reaction (RT-PCR) assay for severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) on nasopharyngeal swab or those being treated for suspected Covid-19 on clinical and radiological evidence of Covid-19 on chest radiograph or computed tomography. 6 Patient demographics and co-morbidities classified using the Charlson comorbidity index were extracted from patient records and our local clinical coding department. 7 The peak PCT concentration recorded during the critical care admission was used, with a cut-off value of 0.5 ng/dL as per local laboratory guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Many radiological societies have advised not to use CT chest for disease screening, especially in asymptomatic patients, as the CT scan has low specificity in differentiating other non-COVID-19 lung infections that could have similar CT chest findings [3,4]. However, recent Cochrane systematic review reported a sensitivity of 87.9% and a higher specificity of 80% in diagnosis of COVID-19 indicating that accuracy may be sufficient for there to be a role for CT in the diagnostic pathway for COVID-19 patients [5].…”
Section: Introductionmentioning
confidence: 99%